PROPAGATION OF MANIPURI DANCE TO THE WORLD - Hemantakumar, Yaikhom; DEVI, LAISHRAM HEMANTAKUMARI (International Journal of Research -GRANTHAALAYAH, 2021)
The then Manipur was a sovereign state ruled by a lineage of many kings. Inspite of being situated in a far, isolated place from other lands and countries and also surrounded by ranges of hills with thick forestation, the inhabitants of this place faced untold hardship in communicating with other external lands and countries. But the state is now recognised by the outside world due to its rich storage of custom, tradition and culture of dance and music. Indeed, it is very surprising and happy when we think of the matter. That we cannot but remember afresh and count the Universal poet Guru Rabindranath Tagore, the descendants of king of Tripura and Miss Luis Lightfoot of Australia and all dedicated and pioneer preceptors in the field of dance.